PAH Distribution and Combustion Sources in Tigris River Sediments: Distribusi dan Sumber Pembakaran PAH dalam Sedimen Sungai Tigris - Salah M. Saleh; Fadhil J. Farhan; Huda H. AL-Kayoon; Maha K. AL-Mishrey; Ali H. Amtegie; Hamid AL-Saad (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Polycyclic aromatic hydrocarbons are persistent organic pollutants that accumulate in aquatic sediments and pose ecological and health risks. Specific Background The Tigris River at Amara City is exposed to urban, industrial, and hydrological pressures that may promote PAH accumulation. Knowledge Gap However, detailed information on PAH concentrations and sources in this river section remains limited. Aims This study aimed to assess the concentration, spatial distribution, and sources of PAHs in surface sediments along the Tigris River at Amara City. Results Sediment samples from five stations were analyzed using GC–MS, revealing total PAH concentrations ranging from 2.73 to 206.05 ng/g, with a pronounced hotspot at Station 5. High molecular weight PAHs dominated most stations, and diagnostic ratios indicated predominantly pyrogenic sources, with minor petrogenic input at one station. Novelty This study provides site-specific evidence of localized PAH contamination and source patterns within a critical reach of the Tigris River. Implications The findings offer baseline data for environmental monitoring and support pollution management strategies in southern Iraq. Keywords: General Background Polycyclic aromatic hydrocarbons are persistent organic pollutants that accumulate in aquatic sediments and pose ecological and health risks. Specific Background The Tigris River at Amara City is exposed to urban, industrial, and hydrological pressures that may promote PAH accumulation. Knowledge Gap However, detailed information on PAH concentrations and sources in this river section remains limited. Aims This study aimed to assess the concentration, spatial distribution, and sources of PAHs in surface sediments along the Tigris River at Amara City. Results Sediment samples from five stations were analyzed using GC–MS, revealing total PAH concentrations ranging from 2.73 to 206.05 ng/g, with a pronounced hotspot at Station 5. High molecular weight PAHs dominated most stations, and diagnostic ratios indicated predominantly pyrogenic sources, with minor petrogenic input at one station. Novelty This study provides site-specific evidence of localized PAH contamination and source patterns within a critical reach of the Tigris River. Implications The findings offer baseline data for environmental monitoring and support pollution management strategies in southern Iraq. Keywords: PAHs, River Sediments, GC–MS Analysis, Source Identification, Tigris River Key Findings Highlights: Marked spatial variability in sediment contamination was observed among sampling stations. Combustion-derived compounds dominated most sampling locations. A localized hotspot exhibited elevated carcinogenic compound levels.